Design of teaching workbench to determine loss of load in piping and connections (Research, Society and Development, 2020)
The purpose of this work was to design a didactic bench, for the practical classes of fluid flow, elevating systems, flow machines and pump calculations, that would allow students to apply, in practice, the concepts learned, in theory, in classroom. On the market, this type of didactic bench usually works only on some aspects of the disciplines of fluid mechanics and flow machines, so schools need to have more than one bench model, which makes it costly. The project was fully modeled in 3D CAD and has a pipeline divided into eight segments, two water pumps, which will allow teachers and students, after reaching the bench, to perform different pressure loss calculations, with the pumps operating in series, in parallel, or single pump, in addition to several types of connections and control valves. The main activities to be carried out will be the calculation of the losses of loads distributed and located in pipes, and accessories, determine the type of flow through the Reynolds number, the flow and speed measurements of the flow through the Venturi tube, trace the pressure curve x pump flow, identify the various components of an industrial pipeline and conduct research in the area of ​​fluids. The project involved students, in the various engineering disciplines, thus complementing their learning and placing them in a real situation of product development. The results obtained were an integrated project with low manufacturing cost projection and the possibility of expansion to other applications.